Serum Zinc Concentration Correlates With Ferritin Concentration in Patients Undergoing Peritoneal Dialysis: A Cross-Sectional Study - Kaneko, Shohei; Morino, Junki; Minato, Saori; Yanai, Katsunori; Mutsuyoshi, Yuko; Ishii, Hiroki; Matsuyama, Momoko; Kitano, Taisuke; Shindo, Mitsutoshi; Aomatsu, Akinori; Miyazawa, Haruhisa; Ueda, Yuichiro; et al. (Frontiers in Medicine, 2020)
Background: Zinc deficiency is common and is associated with erythropoietin resistant anemia, dysgeusia, and hypogonadism in patients undergoing hemodialysis. However, the prevalence and clinical effects of zinc deficiency in patients undergoing peritoneal dialysis (PD) have not been determined. Methods: This was a retrospective, cross-sectional study. The prevalence of serum zinc deficiency and the clinical factors related to serum zinc concentration were determined in 49 patients undergoing PD [mean age 59.5 years (±14.8 years), 38/49 were men (78.6%), median PD period 24.0 months (12.5–45.0 months)]. A serum zinc concentration <60 μg/dL was defined as serum zinc deficiency, and a serum zinc concentration between 60 and 80 μg/dL as possible serum zinc deficiency. Results: Serum zinc deficiency was present in 51% (25/49) of the patients, and possible serum zinc deficiency was present in 45% (22/49) of patients undergoing PD. Multivariate analysis showed that serum zinc concentration significantly correlated with serum ferritin concentration (β = 0.357, P < 0.01). Conclusions: The prevalences of serum zinc deficiency and possible serum deficiency are high and serum zinc concentration correlates with serum ferritin concentration in patients undergoing PD.